The statutes of the Transylvanian Romanians from Făgăraș (1508): a historical perspective and a comparison with the Transylvanian Saxon and Szekler customary laws - Vizauer, Victor V. (Balcanica Posnaniensia. Acta et studia, 2024)
The document known as Statutele Făgărașului (The Statutes of Făgăraș), issued on 15 May 1508, can be considered a monument of old Romanian legislation. The Latin original document was published for the first time in 1885 (in Hungary) and then in 1921 (in Romania). Over the years several authors have translated short parts of the text, which they considered to be of interest for their own research, but a full translation into modern languages was never made until now. Our study solves this problem, rendering in the annex the full transcription and translation of The Statutes of Făgăraș. First, I offer a brief presentation of the historical evolution of the medieval Land of Făgăraș (Țara Făgărașului) from the 14th century until 1508, the year of the document’s issuance. Then I explain how the historical framework facilitated the preservation of the Romanian legal traditions and practices, and we indicate the various articles of the Statutes which reflect specific aspects pertaining to the way of life and the customary law of the Romanians – nobles or lowborn – from Făgăraș. Last but not least, I made a comparison between The Statutes of Făgăraș and the customary laws of the Saxons and Szeklers from Transylvania in the same timeframe.